Plasma iron controls neutrophil production and function - Frost, Joe; Wideman, Sarah K.; Preston, Alexandra E.; Teh, Megan R.; Ai, Zhichao; Wang, Lihui; Cross, Amy; White, Natasha; Yazicioglu, Yavuz; Bonadonna, Michael; Clarke, Alexander J.; Armitage, Andrew E.; et al. (Science advances, 2022)
Low plasma iron (hypoferremia) induced by hepcidin is a conserved inflammatory response that protects against infections but inhibits erythropoiesis. How hypoferremia influences leukocytogenesis is unclear. Using proteomic data, we predicted that neutrophil production would be profoundly more iron-demanding than generation of other white blood cell types. ...
Gesehen am 29.11.2023